DESKRIPSI BAHASA CYBERBULLYING DI MEDIA SOSIAL DAN KAITANNYA DENGAN TINGKAT KEPERCAYAAN DIRI REMAJA - Wulandari, Ratna Rizky; Lestari, Ni Kadek Puja; Febrianty, Alexa; Pramudhita, Hana Shakira; Tahara, Syifa (Jurnal TEDC; Vol 20 No 1 (2026): JURNAL TEDC, 2026)
The increasingly widespread use of social media has intensified adolescents’ engagement in digital spaces, simultaneously creating opportunities for cyberbullying through the use of negative language in online interactions. Language on social media is characterized by its informal register, emotive expressions, and a tendency to be less regulated. This study aims to describe the forms of cyberbullying language on social media and to examine its impact on adolescents’ self-esteem who are active social media users. Data were collected through observations of comments and posts across various social media platforms, supported by documentation in the form of screenshots. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The findings indicate that cyberbullying language is conveyed both explicitly and implicitly, encompassing insults related to physical condition and appearance, as well as stigmatization based on social status and economic class. The impacts include diminished self-esteem, fear of self-expression, and a tendency toward social withdrawal. This study underscores that cyberbullying language exerts a significant influence on adolescents’ self-esteem and highlights the need for preventive efforts through digital literacy and the promotion of respectful language use on social media.